Demography of feral horses (Equus caballus): A long-term study in Tornquist Park, Argentina - Scorolli, Alberto Luis (2010)
Context. All over the world, invasive alien mammals present conservation problems. Feral horses are invasive in many countries and their management is challenging. Aims. To determine the demography of feral horses in Tornquist Park, Argentina, so as to develop a quantitative basis for their management. Methods. Ground counts of individually identified female horses were conducted monthly from 1995 to 1997 and from 2000 to 2002, and seasonally in 1998 and 1999. We calculated the age structure, foaling and survival rates of mares and analysed the effects of adult density and rainfall on demographic parameters. The population trend was calculated by fitting a logistic equation to annual adult mare counts. Key results. The foaling rate averaged 0.55 annually and the survival rate in females averaged 0.89 for adults, 0.91 for juveniles, 0.87 for yearlings and 0.94 for foals. We found adult density, rainfall and the previous year's rainfall to have a significant effect on fecundity but no effect on adult, juvenile and foal female survival rates. Adult density had a significant negative effect on female yearling survival; however, the effect is probably trivial. The logistic equation parameters gave r = 0.327 and carrying capacity (K) = 240 adult mares. Conclusions. A density-dependent response is suggested. The population growth is mainly limited by low fecundity, with the reduced adult female survival probably also playing a minor role. Implications. It is expected that the present long-term demographic study will contribute to the understanding of feral ungulate ecology and improve the management of feral populations. © CSIRO 2010.